Making a Living: African Canadian Workers in London, Ontario, 1861–1901 - Adams, Tracey (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2011)
Abstract There is a growing body of research on African Canadians in the 19th century that touches on their experiences in the workforce. Nonetheless, the literature has been largely silent on how labour market opportunities for African Canadians altered over time and, in particular, how members of this community fared with the slow, but nonetheless dramatic, rise of an industrial-capitalist economy. This study uses census data to explore the occupational experiences of African Canadians living in London, Ontario, between 1861 and 1901. Findings suggest that labour market opportunities were better for men of African origins around mid-century but declined noticeably in the succeeding years. African Canadians of both genders were largely excluded from growth areas in the economy, and their labour was highly concentrated in a narrow range of low-skill jobs. Although there is limited evidence of upward occupational mobility over time for some, and a slight broadening of occupational opportunities by 1901, African Canadian men and women were disadvantaged compared to their white counterparts.